Phytochemical Composition and Pharmaceutical Potential of Lantana sp: A Review - Ravi, Dr. Lokesh (Asian Journal of Pharmaceutics (AJP), 2020)
Lantana is a common plant found in around 60 tropical and subtropical countries worldwide. It is a highly invasive species that has tremendously dominated over other species of plants and threaten biodiversity. At present, physical, chemical, and biological agents are in consideration to eradicate this plant to prevent the threat to biodiversity and soil fertility. Lantana is considered as an unwanted plant and its biomass is disposed off. In this review, the pharmaceutical potential of this plant and its phytochemical constituents are discussed. Being source for wide variety of bioactive phytochemicals, Lantana is a valuable pharmaceutical raw material. Hence, instead of eradicating the plant as waste material, its pharmaceutical potentials such as antioxidant, antidiabetic, antimicrobial, anti-inflammatory, and anticancer activities can be exploited for the possible application as therapeutic agent. The modern medicine can take advantage of the fast-growing nature of this plant and use this plant as a tool for biopharming. In traditional medicine, Lantana has been used in formulation along with other plants as a treatment for several ailments. This review concludes that Lantana is a medicinally valuable plant, with huge potential in the pharmaceutical industry.